INNOVATIVE SOLUTIONS FOR ENERGY-EFFICIENT HYDROGEN PRODUCTION: PROSPECTS FOR UKRAINE - KRAVCHYK, Yuriy; KATKOVA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The aim of this scientific article is to analyze and justify innovative solutions aimed at enhancing the energy efficiency of hydrogen production, with a focus on the prospects for their implementation in Ukraine. The article examines the development of hydrogen energy as a crucial stage in the transition towards a sustainable energy future. Ukraine has significant potential for the deployment of hydrogen technologies due to its natural resources, such as solar and wind energy. However, despite these opportunities, hydrogen production remains energy-intensive, highlighting the importance of developing innovative technologies to reduce energy consumption.One of the key aspects is the improvement of electrolysis technologies, as well as the implementation of new methods for hydrogen transportation. The article also emphasizes the need to overcome technical and economic barriers that hinder the development of hydrogen energy in Ukraine. In particular, recent advancements in electrolyzer technologies, such as alkaline and proton exchange membrane (PEM) electrolyzers, are discussed, along with achievements in hydrogen transportation that open new opportunities for its commercial use.The development of innovations in hydrogen production helps reduce dependence on critical materials, extend the lifespan of electrolyzers, and improve their efficiency. Considering global trends, Ukraine has the potential to integrate hydrogen into its national energy system, especially through the development of infrastructure for hydrogen storage and transportation. Notably, innovations in membrane technologies, such as the development of new membranes for electrolyzers, can significantly enhance hydrogen production efficiency while reducing the use of precious metals.The article also explores Ukraine’s potential participation in international projects, such as HORIZON-JTI-CLEANH2-2024-02-04, aimed at improving hydrogen compression and transportation technologies. This would contribute to lowering the costs of green hydrogen production and increasing energy efficiency.
Keywords: hydrogen energy; energy efficiency; hydrogen production; renewable energy sources; electrolyzers; innovative technologies; infrastructure; transportation